2009
DOI: 10.1001/archgenpsychiatry.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antipsychotics on the High-Affinity State of D2 and D3 Receptors

Abstract: Antipsychotics block both the high- and low-affinity states of the D(2) receptors across the brain, but antipsychotic treatment does not block the [(11)C]-(+)-PHNO signal in the D(3) receptor-rich regions, despite the ongoing D(2) receptor blockade. This [(11)C]-(+)-PHNO signal in regions such as the globus pallidus seems increased despite antipsychotic treatment and is displaceable by a D(3) receptor-preferring agonist. The radiotracer [(11)C]-(+)-PHNO and the data open up new avenues for exploring the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 60 publications
4
64
0
2
Order By: Relevance
“…The reason of this discrepancy with our results is unclear. But, differences in the sample characteristics between postmortem studies and our data such as age (old vs young), length of illness (years vs months), and previous exposure to antipsychotic medications (Graff-Guerrero et al, 2007) may help to explain the discrepancy on the results.…”
Section: Discussionmentioning
confidence: 57%
“…The reason of this discrepancy with our results is unclear. But, differences in the sample characteristics between postmortem studies and our data such as age (old vs young), length of illness (years vs months), and previous exposure to antipsychotic medications (Graff-Guerrero et al, 2007) may help to explain the discrepancy on the results.…”
Section: Discussionmentioning
confidence: 57%
“…Nevertheless, the clinical importance of the D3 receptor to clozapine's clinical effect is likely small, as the D2 occupancy of therapeutic clozapine (20-60%) (Kapur et al, 1999;Nordstrom et al, 1995) is typically less than for the other antipsychotic, indicating that clozapine's D3 receptor occupancy in the clinical setting is likely also much lower than the 35% occupancy seen here. Indeed the recent PET study by our group in schizophrenic patients found that chronic clozapine treatment, while producing B50% occupancy in STR, did not reduce [ 11 C]-( + )-PHNO binding in the GP (Graff-Guerrero et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…In general agreement with the distribution of D2 and D3 receptors, [ 11 C]-( + )-PHNO binding sites in CAU and PUT are thought to represent primarily D2 receptors, whereas those in GP and SN are thought to be primarily of the D3 receptor type (Ginovart et al, 2007;Narendran et al, 2006;Willeit et al, 2006). The pharmacological dissimilarity between [ 11 C]-( + )-PHNO binding sites in CAU/PUT and GP was first suggested by their anatomical distribution and the slower washout of the radiotracer from GP than from CAU and PUT (Ginovart et al, 2007;Willeit et al, 2006), but has since been supported by pharmacological evidence showing that [ 11 C]-( + )-PHNO binding potential with respect to non-displaceable binding (BP ND ) in the GP can be blocked in a regionally selective manner by the D3-selective drugs BP897 and SB277011 in baboon (Narendran et al, 2006;Rabiner et al, 2009), and pramipexole (Graff-Guerrero et al, 2009) and ABT-925 (Graff-Guerrero et al, 2008) in human. Further support for the binding of [ 3 H]-( + )-PHNO to both receptor subtypes is provided by mouse experiments showing that D2 receptor knockout abolishes [ 3 H]-( + )-PHNO binding in the striatum (STR) while leaving SB277011-sensitive binding in midbrain and cerebellum lobes 9 and 10 largely intact (Rabiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results are suggestive of a decline in DRD3 binding with age, in particularly among ADP. No previous [ 11 C]PHNO study has reported a relationship between age and DRD2/3 binding (Boileau et al, 2009;Boileau et al, 2012;Ginovart et al, 2007a;Graff-Guerrero et al, 2009a;Graff-Guerrero et al, 2009b;Shotbolt et al, 2012a;Willeit et al, 2006), which could be due to the narrower age range in their reports and/or to the effect of alcohol.…”
Section: D3 Receptors In Alcoholismmentioning
confidence: 97%